Discovery and genetic analysis of novel coronaviruses in least horseshoe bats in southwestern China - Lihua Wang; Shihong Fu; Yuxi Cao; Hailin Zhang; Yun Feng; Weihong Yang; Kai Nie; Xuejun Ma; Guodong Liang (Emerging Microbes and Infections, 2017)
To investigate bat coronaviruses (CoVs), we collected 132 rectal swabs and urine samples from five bat species in three countries in southwestern China. Seven CoVs belonging to distinct groups of severe acute respiratory syndrome (SARS)-like CoVs and α-CoVs were detected in samples from least horseshoe bats. Samples from other bat species were negative for these viruses, indicating that the least horseshoe bat represents one of the natural reservoirs and mixers for strains of CoVs and has a pivotal role in the evolution and dissemination of these viruses. The genetic and evolutionary characteristics of these strains were described. Whole-genome sequencing of a new isolate (F46) from a rectal swab from a least horseshoe bat showed that it contained 29 699 nucleotides, excluding the poly (A) tail, with 13 open reading frames (ORFs). Phylogenetic and recombination analyses of F46 provided evidence of natural recombination between bat SARS-like CoVs (Rs3367 and LYRa11) or SARS-CoV (BJ01), suggesting that F46 could be a new recombinant virus from SARS-like CoVs or SARS-CoVs.Emerging Microbes & Infections (2017) 6, e14; doi:10.1038/emi.2016.140; published online 29 March 2017